2005
DOI: 10.1007/s00418-005-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

The normal cellular prion protein (PrPc) is strongly expressed in bovine endocrine pancreas

Abstract: Expression of the cellular prion protein (PrP(c)) has been shown to be crucial for the development of transmissible spongiform encephalopathies and for the accumulation of the disease-associated conformer (PrP(sc)) in the brain and other tissues. One of the emerging hypotheses is that the conversion phenomenon could take place at the site where the infectious agent meets PrP(c). In this work we have studied whether PrP(c), a protein found predominantly in neurons, could also exist in pancreatic endocrine cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
3
13
0
Order By: Relevance
“…b-Cell specific aggregation of PrP C A Strom et al in islet cells. 18,33 However, the expression of PrP C in islets of Langerhans has not been linked with glucoregulation nor has it been reported in animal models of diabetes. In this study, we demonstrate that PrP C is strongly expressed in islets and forms b-cell-specific cytosolic aggregates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…b-Cell specific aggregation of PrP C A Strom et al in islet cells. 18,33 However, the expression of PrP C in islets of Langerhans has not been linked with glucoregulation nor has it been reported in animal models of diabetes. In this study, we demonstrate that PrP C is strongly expressed in islets and forms b-cell-specific cytosolic aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] However, the key events leading to immune-mediated b-cell destruction as well as abnormalities in the target b-cells remain unclear. 17 Although it is known that PrP C is abundantly expressed in the endocrine pancreas, 1,18 there are no reports linking PrP C and glucoregulation. In addition, PrP C expression has not been described in animal models of diabetes.…”
mentioning
confidence: 99%
“…PrP c is the substrate for the formation of pathologyassociated conformer PrP Sc (36). However, studies on PrP c distribution in cattle are limited (37)(38)(39). although quantitative studies of PrP c expression at the protein level have been documented in sheep, none have been attempted in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that chicken somatotropes and mammotropes independently appear in diVerent lobes of pituitary gland and that transdiVerentiation from somatotropes to mammotropes is not the central route for diVerentiation of mammotropes in the embryonic chicken pituitary gland. Amselgruber et al (2006) have studied whether cellular prion protein (PrP(c)), a protein found predominantly in neurons, also exists in pancreatic endocrine cells since neuroectoderm-derived cells and pancreatic islet cells share a large number of similarities. For this, the expression of PrP(c) was analyzed in a series of fetal and postnatal bovine pancreatic tissues by immunohistochemistry and RT-PCR.…”
Section: Hormone Cell Biologymentioning
confidence: 99%